El Excentrico, 1964-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1964 [20 de mayo de 1964], Ano 14, No 15, Cover has the photo of John Castro, who was running for supervisor of San Jose. The headline reads "Be Sure to Vote Tuesday June 2."